PENDEKATAN PEDAGOGIK UNTUK MENGATASI KEBERAGAMAN (KEMAMPUAN DAN GAYA BELAJAR) DALAM RUANG KELAS - Resti Hidayat; Babang Robandi; Putri Fajriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The diversity of students in the classroom, both in terms of academic ability and learning styles, is a big challenge for teachers in creating and implementing effective learning. The purpose of this study is to find out the educational methods that can be used to handle diversity so that each student can reach their best potential. Variations in ability levels, backgrounds, and learning style preferences are included in the diversity of students. To address this, a flexible and responsive approach to education is essential. The study suggests the use of "differentiation strategies" in learning. This strategy allows teachers to tailor materials, approaches, and learning media to meet the needs of each student. Additionally, it is essential to create a welcoming learning environment, support students' social-emotional growth, and increase their desire to learn. The results of the study show that this method not only increases student participation but also improves their academic performance. Therefore, teachers can optimize the learning process and ensure that the diversity of students can help achieve the goals of inclusive and quality education.